Effect of different doses of acute gamma radiation on the cultivation of Volvariella volvacea - Fisol, Fatin Nabilah; Abdullah, Sumaiyah; Mohamad, Azhar; Tengku Muda Mohamed, Mahmud; Misran, Azizah; Salim, Sabiha; Azhar, Badrul (Friends Science Publishers, 2022)
In mushroom cultivation, acute gamma radiation can be used and studied to improve the production of its fruiting body. Therefore, the objective of this study was to investigate the effect of gamma radiation on the mycelial growth and production of the fruiting body of Volvariella volvacea (Bull.) Singer. The mycelia were exposed to gamma radiation at various doses: 0 (control), 300, 600, 900, 1200 and 1500 Gy. The irradiated mycelial growth rate was recorded on potato dextrose agar (PDA) and spawning substrate. The spawn was then produced by inoculating the treated mycelia on paddy straw and subsequently cultivated on an empty fruit bunch to compare the production. The result showed no significant difference in mycelial growth rate on wheat, the number of mushrooms, and mushroom weight between control and treatments of 300, 600 and 900 Gy. However, there was the presence of hairy structures on the fruiting bodies of V. volvacea in all spawns with irradiated mycelia and the production of clustered fruiting bodies from spawns treated with 1200 Gy observed. The effect of treatments on the texture of fruiting bodies was insignificant. Although acute gamma radiation did not significantly increase the production of V. volvacea compared to the control treatment, there were morphological changes observed on the V. volvacea fruiting body which can be studied further.